Atypical Forms of Employment in Lithuania: Main Characteristics and Prevalence - Miežienė, Rasa; Gruževskis, Boguslavas (Socialiniai tyrimai, 2016)
The article analyses the types of atypical forms of employment and their spread in Lithuania in the context of the European Union. A special emphasis in the article is laid on security of atypical workers in the labour market. The literature analysis carried out in the article revealed that despite certain advantages of atypical employment atypical employees are less secure in the labour market than employees in standard employment. This insecurity is determined by more frequent stresses due to work-related situations, poor visibility regarding the future level of income and career perspectives. The analysis of statistical data revealed that self-employment and part-time work are the most prevalent atypical forms of employment in Lithuania. A special mention should also be given to two atypical forms of employment – selfemployment and temporary agency work – which have grown most over the past few years in Lithuania.
Keywords: atypical employment; atypical employees; job security; atypical employment contracts